Strategi Kepemimpinan Kepala Sekolah Dalam Menanamkan Pendidikan Karakter Islami Di SMP Negeri 19 Kabupaten Raja Ampat - Kadir, Abdul; Nur, Indria; Dg. Liwang, Asmita Wulansari; Hasbullah, Hasbullah; Ikmal, Ikmal (Tasamuh: Jurnal Studi Islam, 2025)
SMPN 19 Raja Ampat has a mission to instill Islamic character values in the school. This can be seen in the students' daily habits when the researcher visits the school. Thus, the researcher is interested in finding out more about the principal's leadership strategy in instilling Islamic character education in students at SMP Negeri 19 Raja Ampat Regency. Hopefully, these findings can be a good practice reference for schools or other stakeholders implementing Islamic characters among students. This type of research is qualitative research. The results of the research show that the principal's leadership strategy to instill Islamic character education at SMP Negeri 19 Raja Ampat Regency is to optimize the school's vision, mission, and goals, implement exemplary leadership attitudes, instill an attitude of tolerance, and improve the quality of teachers and staffs. The supporting factors are the support of students' parents, collaboration with teachers and staffs, and the existence of supporting facilities and infrastructure. The challenges faced are the influence of social media (information and communication technology), the availability of facilities that do not yet support it, and the awareness of students. The impact of the principal's leadership strategy to instill Islamic character education at SMP Negeri 19 Raja Ampat Regency is to foster harmony in the lives of the people religion in the school environment, increase discipline, and increase public trust.